2018
DOI: 10.17816/ecogen16211-23
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic identification of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhiza (AM) is a widespread symbiosis formed by most land plants with fungi from Glomeromycotina subdivision. The main problem in study of AM fungi is the complication in identification, associated with high intra- and interspecific genetic polymorphism, as well as obligate status of AM fungi in relation to host plant. The methodology for AM fungi identification is constantly undergoing major changes. In the review the selection of optimal methods of molecular genetic identification for AM fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…For example, some works mentioned that different sets of taxa can be detected in the analysis of fungal ITS1 and ITS2 [7][8]. Results of some studies, including those we conducted earlier [1,5,9], showed the detected AMF sequences very often have significant differences from sequences presented in the databases. For example, the NCBI database contains <50% of AMF species [4][5].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, some works mentioned that different sets of taxa can be detected in the analysis of fungal ITS1 and ITS2 [7][8]. Results of some studies, including those we conducted earlier [1,5,9], showed the detected AMF sequences very often have significant differences from sequences presented in the databases. For example, the NCBI database contains <50% of AMF species [4][5].…”
Section: Introductionmentioning
confidence: 95%
“…Morphological identification often does not allow a clear separation of closely related species [1]. At the same time, views of various authors on the systematics of Glomeromycotina radically differ [2].…”
Section: Introductionmentioning
confidence: 99%
“…Certain successes have been achieved in studying the role of endomycorrhiza and its most common form -arbuscular mycorrhiza (AM), which is typical for most modern phylogenetic groups of plants and is introduced in all biomes of the globe. It is formed by fungi belonging to the Glomeromycotina subdivision of the Mucoromycota division (Yurkov et al, 2018). However, the use of arbuscular mycorrhizal fungi (AMF) in crop production is limited, which is a consequence of their obligate symbiotrophy (Ijdo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Different sets of fungal taxa can be discovered by using ITS1 and ITS2 as barcodes [8][9]. Many detected in experimental studies sequences of AM fungi are absent in genetic databases [2,6,10]. The greatest database GenBank NCBI contains less than 50% of found species of AM fungi [5][6].…”
Section: Introductionmentioning
confidence: 99%